Participatory Budget and the Sars-Cov-2 Pandemic in Poland - Jakub Baranowski (Transylvanian Review of Administrative Sciences, 2020)
The SARS-CoV-2 pandemic has affected almost every aspect of social life. Public authorities are trying to combat the effects of the pandemic by introducing specific legal regulations. Even though the Polish legislature has established a number of regulations to combat the epidemiological threat, they have not regulated the participatory budget process. The obligation to establish it, especially in cities with powiat rights (a city with powiat rights should be understood as a city with over 100,000 residents, governed by a mayor), at a time when local government units seek savings, may result in some important investments not being made. On the other hand, maintaining the involvement of residents in the development of local communities can have a positive impact on participation in the community. In this article, the author attempts to analyze the legal situation of participatory budgets during the SARS-CoV-2 pandemic under Polish legislation, at the same time indicating the possibilities of developing this form of civic participation by using, among other things, technologies that enable remote communication.